O comércio internacional de tecnologias ambientais: a inserção do Brasil e da China - Nascimento, Renata Muniz do [UNESP] (2015)
This thesis analyzes international trade in environmental technologies between the years 2002 and 2013 with four objectives: (1) analyze the pattern of international trade to verify the hypothesis of the existence of a north-south pattern, in which the member countries of the OECD, represented by developed countries, leading exports and non-OECD countries, represented by developing and least developed countries, practically limited to the status of importers of environmental technologies; (2) to analyze the insertion of Brazil in international trade of environmental technologies, in particular the performance of its trade balance in this segment; (3) in a similar manner and for purposes of comparison with Brazil, analyze the inclusion of China in international trade in environmental technologies; and (4) assess the level of tariff protection on imports of environmental goods in the OECD group compared to the group of non-OECD countries, especially the data of Brazil and China, in order to check whether there was a liberalization of trade in such goods. The results of this study show the maintenance, in aggregate, North-South pattern of international trade in environmental technologies, but the scenery begins to change in China's rise of reason and the US share decline and Japan in this trade. But Brazil has deepened its trade deficit in environmental goods in this period. Regarding the degree of tariff protection, the developed countries have reduced average tariffs of import compared to those applied by developing countries. China keeps an average of very similar to those import tariffs by developing countries. Brazil already applies much higher than average rates of import those practiced by China, which may explain their lack of representation in the international trade of environmental technologies